Grinding the spent nuclear fuel simulating materials for the magnetoplasma separation - Vinnikov, D.V.; Shulgin, N.A.; Katrechko, V.V.; Yuferov, V.B.; Sokolenko, V.I.; Tkachev, V.I.; Ponomarev, A.N.; Buravilov, I.V. (Вопросы атомной науки и техники, 2016)
Consideration is given to the three methods used for the grinding of materials simulating spent nuclear fuel, in
particular underwater spark discharges, the static compression and the laser sputtering. These methods were
compared by measuring the sizes of obtained materials. The preference is given to the methods of static compression
and the pulse laser sputtering. Рассмотрены три метода измельчения материалов, моделирующих твердое ОЯТ: подводными искровыми
разрядами, статическим сжатием и лазерным распылением. Сравнение методов проведено посредством
определения размеров полученного материала. Предпочтительными являются статическое сжатие и
импульсное лазерное испарение. Розглянуто три методи подрібнення матеріалів, що моделюють тверде ВЯП: підводними іскровими
розрядами, статичним стисненням і лазерним розпиленням. Порівняння методів проведено шляхом
визначення розмірів отриманого матеріалу. Переважними є статичне стиснення та лазерне випаровування.